Ethnobotanical applications and antimicrobial potential of the Shorea genus - Mardhiah, Mohd Shahabuddin; Heng Yen, Khong; Nyotia, Nyokat; Isabel Lim, Fong; Agustono, Wibowo (Society For Conservation And Resource Development Of Medicinal Plants, 2025)
As a key member of the Dipterocarpaceae family, Shorea holds longstanding ethnobotanical significance. Bioactive compounds derived from the Shorea genus, which are rich in flavonoids, terpenoids, and stilbenoids, have emerged as promising candidates due to their notable antimicrobial properties. Despite growing interest, current studies remain fragmented and lack a comprehensive review of their ethnobotany and antimicrobial potential, which limits their application in pharmaceutical research. This study aims to address the current research gap b y evaluating the antibacterial effectiveness of Shorea bioactive compounds. This review emphasises the ethnobotanical significance of different parts of Shorea species, including the seeds, leaves, bark, and resin, and further explores their antimicrobial potential, encompassing crude extracts, purified compounds, and nanoparticles synthesised from Shorea species. Ultimately, this review aligns with United Nations Sustainable Development Goal 3 (SDG 2030) on ensuring health and well-being through sustainable healthcare innovations.